Batang may laban? television news program 24 Oras and TV Patrol's reportage of children involved in crime - Limpot, Kristel Agape Bulay 1998-; Villanueva, Gillian N.
When it comes to children, the media is expected to always consider their best interest as the primordial concern when it comes to reporting. With the administration of President Rodrigo Duterte unleashing an anti-drug campaign as well as proposing to lower the minimum age of criminal responsibility, children have found themselves increasingly being subjects and sources of the news. Accordingly, the study sought to determine if primetime television news programs 24 Oras and TV Patrol follow ethical guidelines on reporting on children, which are provided by various media and children's rights institutions. Directed content analysis was employed in the study, and the researchers looked into the two news programs' episodes from January to February 2019 to examine their adherence to the said guidelines. Journalists from the two news programs who have taken part in the production of the news have also been interviewed. The study found that TV Patrol and 24 Oras generally abide by the ethical guidelines, especially when it comes to the protecting the child's right to privacy and dignity. However, some admitted that they are times wherein time constraints become an issue in ethical reporting. All reporters also agree that there can be instances, though very seldom, wherein not adhering to the guidelines is justified.